Actional poetics - Ash She He the performance actuations of Alastair Maclennan, 1971-2020 - Johnston, Sandra; Driver, Chérie; Blair, Paula (Intellect Books, 2021)
Authoritative study of the Scottish born artist Alastair MacLennan who has achieved worldwide renown as a performance artist. Includes comprehensive visual documentation of his performative practice drawn extensively from his archival resources, with essays from leading national and international scholars in the field. 350 colour illustrations.